Aplikasi Kerja Laboratorium Mahasiswa (Aklam) di Sekolah Menengah Pertama Islam Terpadu (SMPIT) School Gowa Kab. Gowa - Suhardiman; Muh. Syihab Ikbal; Mukti Ali; Ulfia Annamira (Faculty of Tarbiyah and Teacher Training, 2023)
Education is a concius effort to develop the potential of human resources (HR) through teaching activities. To be able to create conducive teaching and learning activities and be able to develop effective learning outcomes is the duty and obligation of the teacher as an education teacher. Therefore, teachers directly seek to influence, foster and develop students abilites to become intelligent and skilled human beings. In essence, practicum is a proof of theory, buht because students only refer to teory without any strengthening of uhnderstanding trough practicum, the understanding gained through practicum is usually more memorable and lasts longer, because students are direcly involved in practicum activities and can prove the theory given by the teacher themselves. Thus the Pyhsic Education laboratory Assistant Team intends to carry out an activity with the title Student Laboratory Work Application (AKLAM) at the Integrated Islamic Junior High School (SMPIT) Al- Fityan School Gowa – Kab Gowa, which is designed as a creative response to increasing wise values towards educational professionalism in learning situations. This activity was carried out for four days of implementation by helping the Head of the Laboratory and the Science Laboratory Manager to improve and complete administration related to the laboratory. And be able to increase students knowledge about global warning symptoms, physics practicum in primary schools, coordination of data collection for school practicums, and completion of school laboratory administration as well as improving the quality of practicum learning for the Phyhsics education laboratory assistant team at UIN Alauddin Makassar at the S-1 level to comply with national education standards, in order to improve the quality of education for students of Physics Education Faculty, Tarbiyah and Teacher Training at UIN Alauddin Makassar in the future.